2006
DOI: 10.1136/ard.2006.055343
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in a multiethnic US cohort LUMINA (XLI): factors predictive of self-reported work disability

Abstract: Objective: To examine the risk factors for self-reported work disability in patients from the LUpus in MInorities: NAture vs. Nurture cohort with systemic lupus erythematosus (SLE). Methods: Patients with SLE of Hispanic (Texas and Puerto Rico), African American and Caucasian ethnicity were studied. Work disability was defined by patients' self-report. Only patients known to be employed at the baseline visit were included. The probabilities of self-reporting work disability over time were examined by the Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
73
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 26 publications
14
73
1
1
Order By: Relevance
“…In both studies, the majority of patients who self-reported work disability were also receiving formal benefits. Disability or work status has been associated with demographic factors, including lower levels of education (10 -12,15) and older age (14,15), higher physical job demands (10,15), disease activity (10,11,14) and disease damage (13,14), and clinical features including neurologic symptoms, fatigue, and joint symptoms (4,5,13).…”
Section: Resultsmentioning
confidence: 99%
“…In both studies, the majority of patients who self-reported work disability were also receiving formal benefits. Disability or work status has been associated with demographic factors, including lower levels of education (10 -12,15) and older age (14,15), higher physical job demands (10,15), disease activity (10,11,14) and disease damage (13,14), and clinical features including neurologic symptoms, fatigue, and joint symptoms (4,5,13).…”
Section: Resultsmentioning
confidence: 99%
“…The SF-36 is widely used as a generic instrument for measuring perceived health status in lupus patients and other chronic conditions. Both the physical and mental components of the SF-36 were significantly associated with work disability in the LUMINA (LUpus in MInorities, NAture versus nurture) study (2) in the bivariate analysis, but were not retained in the multivariate analysis. However, in our study, physical and mental limitations remained significant in predicting work disability in individuals with lupus.…”
mentioning
confidence: 99%
“…Of the 38 (37%) patients who left the work force, 16 reported that their disease was the contributing factor (1). The few existing studies of employment in patients with lupus demonstrate that this disease affects work, including loss of employment, reduced working hours, and reduced performance or productivity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Prevalence estimates of those experiencing work loss within 5 years of diagnosis range from 15% to 40% (2,6,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι δηµοσιεύσεις αναφερόνταν σε σύνολο 9.886 πασχόντων από ΣΕΛ και µε συνέντευξη ερωτήθηκαν σχετικά µε την ανικανότητα-ικανότητα για εργασία.΄Ετσι βρέθηκε ότι ο επιπολασµός της ανικανότητας προς εργασία ήταν 20-40% και από αυτούς το 46 % ( 95% CI 40%-52% ) ήταν ικανοί προς εργασία, ενώ το 34% ( 95% CI 24% -44%) ήταν ανίκανοι προς εργασία. Επίσης, βρέθηκε ότι η νόσος συσχετιζόταν µε ψυχο-κοινωνικούς παράγοντες, όπως ηλικία, εθνικότητα, κοινωνικοοικονοµική κατάσταση, µόρφωση, δραστηριότητα και διάρκεια νόσου, πόνο κόπωση, άγχος και νευρολογικές καταστάσεις (Bertoli AM et al 2007, Da Costa et al 1999, Benitha R et al 2007. Επίσης στην ίδια µελέτη βρέθηκε ότι η ανικανότητα προς εργασία του ΣΕΛ, έχει πολύ υψηλό κόστος για την ∆ηµόσια υγεία.…”
Section: συστηµατικός ερυθηµατώδης λύκοςunclassified